Size and Charge Evaluation of Standard Humic and Fulvic Acids as Crucial Factors to Determine Their Environmental Behavior and Impact - Klučáková, Martina (Frontiers in Chemistry, 2018)
In this work, the size and charge of humic and fulvic standards purchased from the International Humic Substances Society are presented and discussed. Since humic acids are only partially soluble in water, their alkaline solutions were used in this study. Fulvic acids were analyzed both in water and NaOH solution. The intensity, volume, and number particle size distribution were obtained by means of dynamic light scattering. It was found that both particle size distribution and zeta potential are influenced by pH and concentration. The average diameter derived from the intensity distribution was determined to by an inadequate indicator of particle sizes of humic substances. Two or three different size fractions were detected in the studied systems. The colloidal stability was higher for humic acids. In the case of fulvic acids, the colloidal stability increased with increasing pH as a result of the dissociation of their functional groups.